1973
DOI: 10.1128/mmbr.37.1.32-101.1973
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and cytological chemistry blue-green algae.

Abstract: Light and temperature. Synchronous growth.66 Means of obtaining pure cultures.66 Growth of single cells .66 Substances ted; Toxins.66 Regulation and Development..67 Biochemical regulation..67 Chromatic variation..67 Development of Nostoc muscorum,..68 Spores (akinetes)...68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(71 citation statements)
references
References 375 publications
(574 reference statements)
0
70
0
1
Order By: Relevance
“…In the absence of combined nitrogen, however, heterocysts differentiate from vegetative cells at regularly spaced intervals along the filaments (Haselkorn, 1978; Adams and Carr, 1981). It is now known that these heterocysts function as the exclusive sites of nitrogen fixation in aerobically grown cultures (Fay et al, 1968;Wolk, 1973;Haselkorn, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of combined nitrogen, however, heterocysts differentiate from vegetative cells at regularly spaced intervals along the filaments (Haselkorn, 1978; Adams and Carr, 1981). It is now known that these heterocysts function as the exclusive sites of nitrogen fixation in aerobically grown cultures (Fay et al, 1968;Wolk, 1973;Haselkorn, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Both types were present in the alga grown in nitrogen-free medium but the intercalary ones were not formed during growth in ammonium medium. These intercalary heterocysts thus behave like those of simple filamentous cyanophytes in that they are suppressed in the presence of ammonium (Fay, 1973;Wolk, 1973) and it is suggested that the function of these heterocysts is to fix gaseous nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Information about heterocyst differentiation is available mainly for simple filamentous cyanophytes (Fay, 1973 ;Wolk, 1973). In these algae, ammonium ions partially or completely inhibit heterocyst formation (Fogg.…”
Section: Introductionmentioning
confidence: 99%
“…Fritsch (1951) attributed the appearance of the granules to the accumulation of the building material of the cell wall. Fogg (1951) showed that the polar granules abound in material which reacts positively to stains for arginine and to the Feulgen reaction, but unlike cyanophycin granules these are insoluble in acids (see, however, Wolk, 1973). I n recent years few details of the composition of the granules have been worked out, but in the light of the physiological relationship between the heterocyst and adjacent cells it is probable that these bodies have special permeability properties.…”
Section: Structurementioning
confidence: 99%